Neuraxial anaesthesia in parturient with cardiac disease - Minati Choudhury (Indian Journal of Anaesthesia, 2018)
Parturient with corrected or uncorrected cardiac problem may undergo neuraxial anaesthesia for several reasons and in different trimesters. The altered physiological state in a parturient is further deranged in the presence of a cardiovascular lesion, producing the added risk to the parturient undergoing a neuraxial block. A detailed evaluation, knowledge regarding cardiovascular disease state, more vigilant monitoring, and a team approach can lead to a successful outcome.